Elevated Atmospheric Co2 Levels Impact Soil Protist Functional Core Community Compositions - C.-Dupont, Alessandra Ö.; Rosado-Porto, David; Sundaram, Indhu Shanmuga; Ratering, Stefan; Schnell, Sylvia; Justus Liebig University Giessen (My University, 2024)
Protists, known as microeukaryotes, are a significant portion of soil microbial communities. They are crucial predators of bacteria and depend on bacterial community dynamics for the growth and evolution of protistan communities. In parallel, increased levels of atmospheric CO2 significantly impact bacterial metabolic activity in rhizosphere soils. In this study, we investigated the effect of elevated atmospheric CO2 levels on the metabolically active protist community composition and function and their co-occurrences with bacteria from bulk and rhizosphere soils from the Giessen Free-Air CO2 enrichment grassland experiment. Metabarcoding sequencing data analyses of partial 18S rRNA from total soil RNA showed that elevated CO2 concentrations stimulated only a few ASVs of phagotrophic predators of bacteria and other microeukaryotes, affecting protist community composition (P = 0.006, PERMANOVA). In parallel, phagotrophic and parasitic lineages appeared slightly favoured under ambient CO2 conditions, results that were corroborated by microbial signature analyses. Cross-comparisons of protist-bacteria co-occurrences showed mostly negative relations between prokaryotes and microeukaryotes, indicating that the ongoing increase in atmospheric CO2 will lead to changes in microbial soil communities and their interactions, potentially cascading to higher trophic levels in soil systems.
Keywords: ddc:630